ADJEKTIVA BAHASA BENUAQ - Nur Bety (Kantor Bahasa Kalimantan Timur, 2019)
This study aims to describe the types and process of adjective formation in Benuaq language using qualitative descriptive methods. Interview, notes, and literature study are instruments for collecting data. It uses descriptive analysis. Based on the results of the study, there are some adjectives in Benuaq language that have prefixes and infixes meaning 'like', 'as', 'same', 'mutual', and 'always'. It is ke-. Confix in Benuaq language is hardly found in the data of this study. The example of confix is se-yaq. That confix is only attached to reduplication of adjectives which means the most or superlative, similar to se-nya in Indonesian. The adjectives in Benuaq language show two main types, namely qualitative adjective denoting qualities and relative adjective expressing membership in a group. Qualitative adjectives express (1) characteristic, (2) size, (3) color, (4) time, (5) distance, (6) opinion, and (7) perception. Relative adjectives place reference bound to a particular group. Their presence cannot be qualified.